Blended Learning and the Development of Tacit Knowledge, Problem?Solving Skills, and Professional Judgment in TVET Students : A Narrative Review - Azni, Mohd Edyazuan; Syahirah Rosli; M.S M. Ghazali; M. Mupit; Zaihar Yaacob; Mohamad Zulkeflee Sabri; Mohd Nizam Zahari; A.A Hamzah (Journal of TVET and Technology Review, 2026)
This narrative review examines the impact of blended learning that integrates online theory and on-site practice in developing the tacit knowledge, problem-solving skills, and professional judgment of TVET students. It frames vocational competence as a multi-faceted concept characterized by technical–conceptual skills, embodied tacit knowledge, high order problem solving and value informed judgment. Building on research into TVET and cognate fields of practice-based learning, the review synthesises evidence about how some blended designs like flipped classrooms, simulation supported practical experiences, project based/purposeful activities and structured reflection, can deepen and expand around authentic tasks. The analysis shows that blended learning can improve vocational expertise when online and on-site components are tightly aligned with real work processes, sustain significant hands-on experience, and provide systematic opportunities for reflection, feedback and moral discussion. In contrast, blended approaches that are primarily intended for content delivery or to minimize physical exposure will have less of an effect on the deeper levels of expertise. The ambivalence of the review ends with a strong premise for blended learning as high promise to TVET, however, the latter is premised upon effective pedagogical and institutional design. It also recommends more longitudinal and design-based research into how certain blended models influence the behaviour and decision making of graduates in real-life work environments.